Sand seas and dune fields of Egypt - Bubenzer, Olaf; Embabi, Nabil Sayed; Ashour, Mahmoud M. (Geosciences, 2020)
The article reviews the state of knowledge about distribution, sizes, dynamics, and ages of all sand seas (N = 6) and dune fields (N = 10) in Egypt (1,001,450 km2). However, chronological data (Optically Stimulated Luminescence, Thermoluminescence), used in the INQUA (International Union for Quaternary Research) dune database, only exists from three of the five sand seas located in the Western Desert of Egypt. The North Sinai Sand Sea and four of the ten dune fields are located near the Nile Valley, the delta or the coast and therefore changed drastically due to land reclamation during the last decades. Here, but also in the oases, their sands pose a risk for settlements and farmland. Our comprehensive investigations of satellite images and our field measurements show that nearly all terrestrial dune forms can be observed in Egypt. Longitudinal dunes and barchans are dominant. Sand seas cover about 23.8% (with an average sand coverage of 74.8%), dune fields about 4.4% (with an average sand coverage of 31.7%) of its territory. For the Great Sand Sea and the Farafra Sand Sea, situated in the central and northern part of the Western Desert, a Late Glacial transformation by strong westerlies was found, but not for the Selima Sand Sea, situated in the south of Egypt. Regarding the sparse chronological data up to now, for a reasonable estimation of future sand mobility in the course of global climate change, further data are essential. Finally, further studies concerning sand mobility, local wind systems, and land use are needed.
Gesehen am 23.04.2021